A case study of classically trained singers in pop singing / Norfazrina Mohd Gani - Norfazrina , Mohd Gani (2020)
In general, this study was conducted to discuss about a classically trained singers in pop singing among professional singers in Malaysia. Therefore, this study is limited only to classically trained singers in singing modern pop’s genre based on vocal techniques and vocal health. The respondents consisted of 5 Malaysian singers who are well trained classically and have experienced in both education and music industry singing pop songs. As a classically trained singer, this study employed narrative inquiry focusing on their life experience using their vocal techniques that they have mastered and to prove that classically trained singers can deliver pop songs better than typical pop singers who are in the industry and at the same time they shared about how important vocal health in singing. The interview was approximately 60 minute each session which is to allow respondent rebuild and share their stories and experiences. Interview was audio-recorded and transcribed. Qualitative data was analysed, the respondents indicated that it is vital to take care of our health because without a good health, they will not going to be a great performance. Collectively, this study has acquire new knowledge that all aspects of vocal techniques and vocal health, A case study on the preparation of vocal warm up, the differences between classical and pop singers in terms of vocal techniques, and the relationship between vocal techniques and vocal health in terms of classical and pop singing is prepared.